Chronic Radiation Proctosigmoiditis in Patients with Cervical Cancer - Juliyanti -; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Complications in rectum and sigmoid due to radiation are usually called radiation proctosigmoiditis. It can be acute or chronic based on the onset of symptoms during radiation treatment. There are some treatment modalities aimed for reducing rectosigmoid bleeding and improving symptoms of chronic radiation proctosigmoiditis, which include medication, endoscopy and surgery. Most data about the effectiveness of those various modalities are provided by short-term studies with small sample size.A female patient, 59 years old, came with a chief complaint of passing persistent fresh bright red bloody stool since 1 year before admission. The patient was then diagnosed with stage IIIB cervical cancer and she received 25 times of external radiation, 3 times of internal radiation and 3 times of chemotherapy.  She was diagnosed with chronic radiation proctosigmoiditis and treatment to stop the bleeding was carried out by performing argon plasma coagulation through colonoscopy. The problems in the patient were formulated as chronic radiation proctosigmoiditis with malnutrition and iron deficiency anemia due to chronic bleeding. Non-pharmacological and pharmacological medications were administered.Keywords: radiation proctosigmoiditis, argon plasma coagulation, medication